2008
DOI: 10.1016/j.devcel.2008.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of a Human Kinetochore by Specific Targeting of Chromatin Modifiers

Abstract: SummaryWe have used a human artificial chromosome (HAC) to manipulate the epigenetic state of chromatin within an active kinetochore. The HAC has a dimeric α-satellite repeat containing one natural monomer with a CENP-B binding site, and one completely artificial synthetic monomer with the CENP-B box replaced by a tetracycline operator (tetO). This HAC exhibits normal kinetochore protein composition and mitotic stability. Targeting of several tet-repressor (tetR) fusions into the centromere had no effect on ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
442
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 244 publications
(470 citation statements)
references
References 62 publications
25
442
3
Order By: Relevance
“…2B). As expected from previous studies (Cardinale et al, 2009;Nakano et al, 2008), in parallel control experiments, interphase HACs targeted by tetR-EYFP retained robust CENP-A staining for at least 2 days after transfection ( Fig. 2A).…”
Section: Acetylated Chromatin Is Compatible With the Integrity Of Thesupporting
confidence: 63%
See 4 more Smart Citations
“…2B). As expected from previous studies (Cardinale et al, 2009;Nakano et al, 2008), in parallel control experiments, interphase HACs targeted by tetR-EYFP retained robust CENP-A staining for at least 2 days after transfection ( Fig. 2A).…”
Section: Acetylated Chromatin Is Compatible With the Integrity Of Thesupporting
confidence: 63%
“…Our experimental system enables us to engineer changes directly in the chromatin of a stable artificial chromosome (the alphoid tetO HAC), whose centromeric DNA contains an array of alpha-satellite repeats containing tetracycline operators (Nakano et al, 2008). Using this system, we previously found that the specific removal of the histone mark H3K4me2 from kinetochore chromatin resulted in a concomitant decrease in the level of transcription of this chromatin in human cells (Bergmann et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations